TRADE OF CARBON CREDITS FROM SPECIALLY PROTECTED AREAS: A SOLUTION TO FUND THE REFORESTATION OF THE AMAZON (VERUM: Journal of Scientific Initiation, 2025)
The study investigates the potential of selling carbon credits from protected areas as a solution to fund the reforestation of the Amazon, addressing the environmental and social benefits of this practice. The research uses a bibliographic review, data analysis on deforestation and reforestation in the Amazon, and case studies of carbon credit projects to assess their feasibility and impact. It was identified that the commercialization of carbon credits not only protects ecosystems and stimulates forest regeneration but also generates resources that can improve the quality of life of local communities by promoting education, healthcare, and sustainable infrastructure. These projects strengthen community participation in the management of protected areas, preserve their cultural traditions, and contribute to social and economic development. Aligned with the UN Sustainable Development Goals, particularly SDGs 13, 15, and 1, the sale of carbon credits reduces greenhouse gas emissions, increases carbon sequestration capacity, and preserves biodiversity while combating inequality and promoting social justice. It is concluded that the carbon credit market is a strategic tool to address the climate crisis, protect conservation areas, and promote a sustainable and inclusive development model.
Keywords: Carbon Credit Trading; Reforestation; Amazon; Deforestation; Environmental Awareness